2018
DOI: 10.1093/intimm/dxy089
|View full text |Cite
|
Sign up to set email alerts
|

A partial agonist for retinoid X receptor mitigates experimental colitis

Abstract: Inflammatory bowel disease (IBD), including ulcerative colitis and Crohn’s disease, is an intractable disease of the gastrointestinal tract. Multiple environmental factors, including food ingredients, have been implicated in the development of these diseases. For example, animal fat-rich diets are predisposing factors for ulcerative colitis, whereas n-3 unsaturated fatty acids such as docosahexaenoic acid (DHA) show protective effects in experimental colitis and are negatively correlated with the incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…As a result, synergistic activation of the RXR/PPARg heterodimer was established by the PPARg agonists rosiglitazone or troglitazone and the RXR agonist retinoid, suggesting protective combined effects against colon inflammation (Desreumaux et al, 2001). Further, a recent study of DSS-induced colitis showed that the partial RXR agonist CBt-PMN was also capable of ameliorating intestinal inflammation in this mouse model of UC through both PPARb/ d/RXR and Nur77/RXR heterodimer activation (Onuki et al, 2019).…”
Section: Role For Pparg In Ulcerative Colitismentioning
confidence: 84%
“…As a result, synergistic activation of the RXR/PPARg heterodimer was established by the PPARg agonists rosiglitazone or troglitazone and the RXR agonist retinoid, suggesting protective combined effects against colon inflammation (Desreumaux et al, 2001). Further, a recent study of DSS-induced colitis showed that the partial RXR agonist CBt-PMN was also capable of ameliorating intestinal inflammation in this mouse model of UC through both PPARb/ d/RXR and Nur77/RXR heterodimer activation (Onuki et al, 2019).…”
Section: Role For Pparg In Ulcerative Colitismentioning
confidence: 84%
“…Conventional full RXR agonists are known to show considerable adverse effects, but the partial RXR agonist, CBt-PMN, efficiently ameliorated the symptoms of colitis. This effect is attributed to the down-regulation of pro-inflammatory cytokines such as Tnf and Il6 in colon-infiltrating monocytes probably by the activation of PPARδ/RXR and Nur77/RXR heterodimers by CBt-PMN (202).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the RXR/PPARα axis inhibits NF-κB transcription activity, and the RXR/PPARβ axis suppresses inflammatory interleukin-6 production. 74,75 Agonist-activated RXR/PPAR complexes negatively regulate other transcription factors including NF-κB and activator protein-1, which are involved in the promotion of CXCL1 and CXCL2 expression, thereby inhibiting its ability to induce gene transcription. 66,[75][76][77][78] For the remaining RXR heterodimer, RXR/LXR, an RXR agonist reduced translocation of NF-κB into nuclei F I G U R E 7 Essential role of retinoid X receptor (RXR)α on 12-hydroxyeicosapentaenoic acid (HEPE)-mediated chemokine suppression in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%